TIPOLOGI IDENTITAS MUSLIM TIONGHOA DI PALEMBANG SUMATERA SELATAN - Zaki Faddad Syarif Zain; Herwansyah Herwansyah (JIA (Jurnal Ilmu Agama), 2017)
This article seeks to describe the existence of the Muslim Chinese in Palembang. So far, the discussion on Chinese Tionghoa always represented by PITI (Persatuan Islam Tionghoa Indonesia) (Persatuan Iman Tauhid Indonesia) or the non muslim Chineses who convert to Islam . However, in the case of Palembang it was found that the Chinese Muslim identity could be divided into two typology, the peranakan Chinese Muslims, the Muslim descendants of China from the 17th and 18th centuries and not from the colonial segregation of colonial politics, but as they recalled their past- social well-established in traditional Islamic society of Palembang. The second group is a converted Chinese, a non-Islamic Chinese convert to Islam. This group is represented by PITI Palembang